Influence of brain types on motor skill coordination - Finch, A.; Niednagel, J.; Finch, L.; Ariel, G. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The influence of a person`s brain type and the segmental coordination used in free throw basketball shooting was evaluated by video analysis. Fifteen subjects were classified using a brain typing inventory with 16 categories. Markers were placed on selected joints of the participants who performed 5 free throws, videotaped in the sagittal plane at 60 Hz. Three participants having a brain type on each end of the personality spectrum were selected for film analysis. The shooting coordinate data was analyzed using an Ariel APAS. The time and maximal angular velocities were calculated for selected joints. The order of joint sequencing was determined for the brain types. Subjects who were brain type (BCIL/INTJ) tended to use multiple joint sequencing and those of brain type (FEAR/ESFP) used primarily large segments.